Het modern socialisme en E. Leburton. - Vandromme, Pol (Brussel : Labor, 1970)
Collectie Vrijzinnige Werkmansbibliotheek
Archief Lucien Boussé
Nederlands
Monografie
Keywords: Leburton, Edmond; Vrijzinnige Werkmansbibliotheek